Rise and fall in ischemic heart disease mortality: it may have happened before - Azambuja,Maria Inês R. (1995)
The rise in ischemic heart disease(IHD) mortality occurring mostly during the first half of the 20th century is usually associated with economic development and its consequences for people's lifestyles. On the basis of historical evidence, it is postulated that a previous IHD epidemic cycle may have occurred in England and Wales towards the turn of the nineteenth century. The implications of this on causal theories and current etiological research on atherosclerosis are discussed.